Pelatihan Dan Pendampingan Pembuatan Media APE Dari Kardus Bekas Pada Guru RA Darussalam - Maria Ulfa (Universitas Muhammadiyah Manado, 2024)
Education today has increasing challenges due to the rapid development of technology and access by kindergarten children. Interest in digital media is higher than the learning process in the classroom which is monotonous or less interesting than digital media. So there is a need to reform the learning process by creating a pleasant learning atmosphere, namely teachers need to have creativity and innovation in building an active learning atmosphere. Efforts that can be made by teachers are to direct the learning process to play with the media of educational game tools by using used items such as cardboard. However, teachers at RA Darussalam have not implemented it. The purpose of this community service is to motivate and provide innovation to teachers in making APE media using used goods, namely cardboard. This research was conducted through community service research methods. The result of this service is to provide teachers with motivation and innovation and provide creative ideas in making APE media without high costs, namely through the use of used barracks around such as cardboard.